"Is My Heart Healing?" A Meta-synthesis of Patients' Experiences After Acute Myocardial Infarction. Issue 5 (September 2021) - Dreyer, Rachel P.; Pavlo, Anthony J.; Hersey, Denise; Horne, Anna; Dunn, Robert; Norris, Colleen M.; Davidson, Larry
Abstract : Background: Recovery from acute myocardial infarction (AMI) has been primarily understood in a narrow medical sense. For patients who survive, secondary prevention focuses largely on enhancing clinical outcomes. As a result, there is a lack of descriptive accounts of patients' experiences after AMI and little is known about how people go about the challenge of recovering from such an event. Objective: We conducted a meta-synthesis of the available literature on qualitative accounts of patients' experiences after AMI. Methods: We searched for relevant papers that were descriptive, qualitative accounts of participants' experiences after AMI across 4 electronic databases (April 2016). Using an adapted meta-ethnography approach, we analyzed the findings by translating studies into one another and synthesizing the findings from the studies. Results: After a review of titles/abstracts, reading each article twice in full, and cross-referencing articles, this process resulted in 17 studies with 224 participants (48% women) aged 23 to 90 years. All participants provided a first-person account of an AMI within the 3-day to 25-year time frame. Two major themes emerged that characterized patients' experiences: navigating lifestyle changes and navigating the emotional reaction to the event—consisting of various subthemes. Conclusion: Although AMI tends to be seen as a discrete event, participants are left with little professional guidance as to how to negotiate significant, and often discordant, psychosocial changes that have long-lasting effects on their lives, similar to persons with chronic illnesses but without research in place to figure out how to best support them.